2020
DOI: 10.3991/ijet.v15i03.10480
|View full text |Cite
|
Sign up to set email alerts
|

The Design of a Learning Process for Promoting Teamwork using Project-Based Learning and the Concept of Agile Software Development

Abstract: The design of a learning process for promoting teamwork using project-based learning and the concept of Agile software development had the following objectives: a) analyze and synthesize the conceptual framework for a learning process for computer students aimed at promoting teamwork using project-based learning and the concept of Agile software development; and b) a evaluate the suitability of a learning management model design for computer students aimed at promoting teamwork via project-based learning and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 15 publications
2
11
0
1
Order By: Relevance
“…Similar results were reported in Ref. (Sakulviriyakitkul et al, 2020), who designed a learning process to promote teamwork using PBL and the concept of agile software development, finding that as these processes were integrated, students demonstrated higher levels of attention, motivation and interest in exchanging ideas and information. Similarly, in 2017 (Chatwattana & Nilsook, 2017) reported the creation of a web system to improve the student learning process through the combination of project-based learning and imagination, which promoted cooperation among students through the pursuit of innovation.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…Similar results were reported in Ref. (Sakulviriyakitkul et al, 2020), who designed a learning process to promote teamwork using PBL and the concept of agile software development, finding that as these processes were integrated, students demonstrated higher levels of attention, motivation and interest in exchanging ideas and information. Similarly, in 2017 (Chatwattana & Nilsook, 2017) reported the creation of a web system to improve the student learning process through the combination of project-based learning and imagination, which promoted cooperation among students through the pursuit of innovation.…”
supporting
confidence: 84%
“…Allowing students to take ownership of research through the project-based teaching model enabled them to understand the issues while being more attentive and motivated (Sakulviriyakitkul et al, 2020). They showed interest not only in wanting to find a solution, but in making connections with their communities (Zhou et al, 2013) by disseminating the results of their research to the educational and rural community, with the aim of using their findings to positively affect the communities in which they live.…”
Section: Discussionmentioning
confidence: 99%
“…Learning is fundamental in human life; by learning, humans make individual qualitative changes so that their behavior develops. Learning is a complex process in every person throughout his life [2], [3]. The learning process occurs because of the interaction between a person and his environment [4].…”
Section: Background/ Objectives and Goalsmentioning
confidence: 99%
“…Sakulviriyakitkul, Sintanakul and Srisomphan [40] found that PBL promotes teamwork in students as well as generates high levels of motivation and interest that encourage the exchange of information for the realization of the project. In addition, they conclude that ICT contribute to supporting the effectiveness of the PBL due to the use of networks and resources that benefit learning.…”
Section: Literature Reviewmentioning
confidence: 99%